TO THE QUESTION OF ENSURING THE HEALTHY GROWTH OF YOUTH - Norkobilov Mukhiddin Najimovich; Odilova Feruzakhon Valijonovna (Journals Park Publishing, 2022)
This article analyzes the issue of ensuring that young people grow up healthy. Ensuring the healthy growth of young people has always been one of the main ideas of pedagogy and creativity of thinkers.
Keywords: sports, physical education, secondary school, folklore, youth, minors, influence.